Association of Vitamin D Levels and type 2 Diabetes Mellitus in Asian Indians is Independent of Obesity - Gupta, A.; Aslam, M.; Rathi, S.; Mishra, B. K.; Bhardwaj, S.; Jhamb, R.; Madhu, S. V. (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background A large proportion of subjects with type 2 diabetes mellitus (T2DM) in India are non-obese. Asian-Indian subjects with diabetes have been shown to have low vitamin D levels. Whether low vitamin D levels and T2DM in Asian-Indians is attributable to the associated obesity as in caucasians is unclear. Hence we studied the association of vitamin D levels and T2DM in Asian-Indians with or without obesity.Methods Total of 213 subjects were recruited in four groups, group 1-Non-obese diabetic, group 2-Non-obese non-diabetic, group 3-Obese diabetic and group 4-Obese non-diabetic. Subjects recruited under various groups were matched for age and sex. Anthropometry, skin-fold thickness, fasting and postprandial plasma glucose, HbA1c, fasting insulin, lipids and vitamin D levels were measured in all study subjects and were compared between the groups.Results Mean age of study population was 41.23±7.43 years. Mean BMI in groups 1,2,3 and 4 was 21.34±1.41, 20.53±2.27, 27.72±2.94 and 27.62±3.37 kg/m2 respectively. Overall 64.3% study subjects had vitamin D deficiency and 27.7% had insufficient vitamin D levels. Significantly lower vitamin D levels were found in diabetic groups 1 and 3 compared to non-diabetic groups 2 and 4. No significant difference was observed in vitamin D levels between groups 1 and 3. Similarly, no significant difference was observed in vitamin D levels between groups 2 and 4. Vitamin D levels did not show any significant correlation with BMI, waist or body fat.Conclusion Vitamin D levels do not appear to be related to obesity in diabetic as well non-diabetic Asian-Indian individuals.
Keywords: Asian indians; diabetes; obesity; Vitamin D